Development and performance of a fast timing micro-pattern gaseous detector (FTM) for future collider experiments and medical diagnostics. (1st February 2022) - Maggi, M.; Pellecchia, A.; Ranieri, A.; Roskas, C.; Sharma, A.; Tytgat, M.; Vai, I.; Verwilligen, P.
Abstract: The fast timing MPGD is a micro-pattern gaseous detector conceived for achieving sub-nanosecond time resolution while maintaining the ability to instrument large areas in high-rate environments; applications of such technology are perspected in high-energy physics experiments at future colliders and medical diagnostics with time-of-flight methods. The work presented is a set of systematic studies carried on an FTM prototype on the performance of GEM foils coated with resistive DLC films, whose development is essential for the FTM operation. The resistive foil performance has been tested with several gas mixtures and compared with the results obtained on conductive foils. The results show that the performance of the FTM is presently limited by the technology of manufacturing of DLC-coated GEM foils, with high gains reachable exclusively in isobutane-based mixtures.